Determinants of virological failure among adults on first-line highly active antiretroviral therapy at public health facilities in Kombolcha town, Northeast, Ethiopia: a case–control study - Habtamu Mengist Meshesha; Zelalem Mehari Nigussie; Anemaw Asrat; Kebadnew Mulatu (BMJ Open)
Objective To identify determinants of virological failure among HIV-infected adults on first-line highly active antiretroviral therapy at public health facilities in Kombolcha town, Northeast, Ethiopia, in 2019.Methods An unmatched case–control study was conducted from April to May 2019. About 130 cases and 259 controls were selected by simple random sampling. Data were extracted from charts of patients using a structured checklist. Multiple logistic regression analysis was performed to identify possible factors. Hosmer-Lemeshow goodness of fit test was used to check the model. Finally, independent predictor variables of virological failure were identified based on adjusted OR (AOR) with 95% CI and a p value of 0.05.Results The odds of virological failure were 2.4-fold (AOR=2.44, 95% CI 1.353 to 4.411) higher in clients aged <35 years compared with older clients, fivefold (AOR=5.00, 95% CI 2.60 to 9.63) higher in clients who did not disclose their HIV status, threefold (AOR=2.99, 95% CI 1.33 to 6.73) higher in clients with poor adherence, and 7.5-fold (AOR=7.51, 95% CI 3.98 to 14.14) higher in clients who had recent CD4 count of ≤250 cells/mm3.Conclusion and recommendation This study revealed that age, marital status, occupation, disclosure status, baseline functional status, missed clinic visit, current antiretroviral therapy regimen, adherence to treatment and recent CD4 count were significantly associated with virological failure. Therefore, adherence support should be strengthened among clients. Missed clinic visits should also be reduced, as it could help clients better adhere to treatment, and therefore boost their immunity and suppress viral replication.